A microporous lanthanum metal–organic framework as a bi-functional chemosensor for the detection of picric acid and Fe3+ ions1. Issue 29 (7th August 2015) - Zhang, Chuanqi; Yan, Yan; Pan, Qinhe; Sun, Libo; He, Hongming; Liu, Yunling; Liang, Zhiqiang; Li, Jiyang
<x xml:space="preserve">Abstract</x> A novel microporous lanthanum metal–organic framework 1 was synthesized by using the rigid unsymmetrical tricarboxylate ligand H3TPT. This compound exhibits selective detection of picric acid (PA) and Fe3+ ion.